Pengaruh Perencanaan Sumber Daya Manusia terhadap Kinerja Dinas Kesehatan Kabupaten Karawang - Dede Ratnaningrum; Sonny Hersona; Dede Jajang Suyaman (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the effect of human resource planning on the performance of the Karawang district health office. The method used in this research is descriptive and verification with a quantitative approach, the sample used in this study is 50. The data analysis used in this research is simple regression analysis with hypothesis testing t test and f test. The results show that the coefficient of 0.288 means about 28.8%, then the HR Planning variable (X1) has a contribution to performance (Y) while the remaining 71.2% is explained by other factors not examined in this study (ε). Based on the results of research related to the influence of human resource planning on employee performance, the value of sig 0.000 is smaller than the alpha value, which is 0.05, it can be concluded that there is a partial effect of the variable human resource planning on employee performance. Based on the results of research related to the influence of human resource planning on employee performance, the value of sig 0.000 is smaller than the alpha value, which is 0.05, it can be concluded that there is a simultaneous influence of the variable human resource planning on employee performance.